MAKNA KEBERADAAN VESPA EXTREME BAGI SCOOTERIST: Fikri Muhamad Ridho , Heri Hendrawan - Jurnal COMMED (Commed : Jurnal Komunikasi dan Media, 2017)
This research is motivated phenomenon rampant vespa extreme use, a vehicle that has been modified vespa was known as extreme, because users produce a wide range of unique vehicles, which adorn the quaint town in Indonesia. Appearance is intentionally made to describe their souls are free to express the impression of what it is. Many vespa has changed into a form that is barely recognizable, either to make them more comfortable or to improve the aesthetics. The purpose of this research is to discover and explain more about the meaning of existence vespa vespa extreme for members of the extreme. This study used a qualitative approach, the method of phenomenology and constructivism. Data collected by interview, observation, literature study and documentation. Researchers took seven informants who are community members vespa extreme in Garut as research subjects to serve as a source of data on the number of questions of interviews conducted by purposive sampling. The results showed that the community members vespa extreme meaning of existence vespa extreme derived from motive "because" community members Vespa Extreme when joining the Community Vespa Extreme, motive "for" community members Vespa Extreme when joining the Community Vespa Extreme, and the experience of communication actions from community members vespa extreme, so it appears the meaning itself of the informant.